How Does Advertising Depend on Competition? Evidence from U.S. Brewing - Chandra, Ambarish; Weinberg, Matthew (Management Science, 2018)
The relationship between market structure and advertising has been extensively studied, but has generated sharply opposing theoretical predictions, as well as inconclusive empirical findings, likely because of severe endogeneity concerns. We exploit the 2008 merger of Miller and Coors in the U.S. brewing industry to examine how changes in local concentration affect firms’ advertising behavior. Well-established regional preferences over beer brands, and the sharp increase in concentration from the merger, make this an excellent setting to analyze this question. We find a significant positive effect of local market concentration on advertising expenditures: a 100-point increase in the Herfindahl–Hirschmann Index measure of concentration increases advertising per capita by about 5%. Our findings shed light on how and when firms choose to deploy advertising. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2889. This paper was accepted by Eric Anderson, marketing.